Pengembangan Produk Usaha Mikro Kecil Menengah Dan Kekayaan Intelektual Atas Batik di Sanggar Batik Krakatoa Kota Cilegon - Sulasno Sulasno; Lolitawati Lolitawati; Putri Pratama Ayu Ningsih (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2024)
Batik is a culture that takes the form of a painting craft. The existence of batik with its beautiful motifs, designs and patterns has made batik art a preserved cultural heritage. This research aims to determine product development for Micro, Small and Medium Enterprises and forms of legal protection for batik in the Krakatoa Batik Studio, Cilegon City. This research uses a qualitative method with an empirical juridical approach. The primary data source comes from the Krakatoa Batik Studio, Cilegon City, while the secondary data comes from books, journals, encyclopedias, dictionaries and virtual sources. while the data processing technique is through interviews. The results of this research show that product development for micro, small and medium enterprises and intellectual property for batik at the Krakatoa Batik Studio in Cilegon City can be carried out by developing models, patterns, colors, batik patterns, variations and development of typical batik. in the Krakatoa studio which has the philosophy of the city of Cilegon, apart from that, it is no less important to collaborate with other batik craftsmen in making goods that have batik motifs, as well as development in terms of marketing, the Krakatoa batik studio has expanded into the online market by having a shop on Bukalapak, and Legal protection for Micro, Small and Medium Enterprises products and Intellectual Property for Batik at the Krakatoa Batik Studio in Cilegon City can be done by registering the intellectual works owned including copyrights, brands and patents to the directorate general of intellectual property to obtain legal rights and protection from the state.